THE ROLE GIS IN THE ASSESMENT OF ELECTROMAGNETIC RADIATION ON THE EXAMPLE OF A RESIDENTAL AREA - Faiz Nursultan Saparulu,; Satayev Marat Isakovich,; Berdaliyeva Aydin Abdullaevna,; Azimov Abdugani Mutalovich,; Shapalov Shermakhan Kuttybayevich,; Nikonov Oleg Yakovlevich, (Academic Journal of Physical and Chemical Sciences, 2021)
Today, one of the important tasks that is set before environmental monitoring is to continuously obtain the necessary data on the state of the environment through the use of remote sensing techniques. It should be noted that remote sensing (hereinafter – RS) is used in the technogenic environment of mankind, which directly creates unfavorable conditions, increasing the statistics of the origin of various types of carcinogenic risks. The growing consumption of electric energy leads to the construction and commissioning of new energy facilities, as well as to the construction of high-voltage power lines in the residential environment. An important task in this direction is the establishment of sanitary protection zones, taking into account environmental restrictions, which is aimed at reducing social tension among the population located in the zone of active exposure to the electromagnetic field. Given that low-frequency energy objects, like other man-made objects, are characterized by dynamic characteristics and require constant monitoring of the course of changes in continuous processes, which directly affects the change in the intensity of the electromagnetic field. In turn, the modern information platform allows you to simultaneously conduct environmental surveys to identify carcinogenic risks in the selected area at a specific time by entering the necessary data, which are the main factors in setting the maximum permissible conditions. The development of digital maps based on Arc GIS application programs has a simulation characteristic and allows you to visually assess the dynamics of environmental changes with different variations